Embracing Robotics in Microsurgery: Robotic-Assisted Deep Inferior Epigastric Perforator Flap Breast Reconstruction - Choe, Joshua; Aiello, Christopher; Yom, Jina; Minasian, Raquel A.; Sugiyama, Gainosuke; Smith, Mark L.; Selber, Jesse C.; Tanna, Neil (Journal of Reconstructive Microsurgery, 2024)
The integration of robotic-assisted surgery (RAS) has transformed various surgical disciplines, including more recently plastic surgery. While RAS has gained acceptance in multiple specialties, its integration in plastic surgery has been gradual, challenging traditional open methods. Robotic-assisted deep inferior epigastric perforator (DIEP) flap breast reconstruction is a technique aimed at overcoming drawbacks associated with the traditional open DIEP flap approach. These limitations include a relatively large fascial incision length, potentially increasing rates of postoperative pain, abdominal bulge, hernia rates, and core weakening. The robotic-assisted DIEP flap technique emerges as an innovative and advantageous approach in fascial-sparing abdominal autologous breast reconstruction. While acknowledging certain challenges such as increased operative time, ongoing refinements are expected to further improve the overall surgical experience, optimize results, and solidify the role of robotics in advancing reconstructive microsurgical procedures in plastic surgery. Herein, the authors provide an overview of robotic surgery in the context of plastic surgery and its role in the DIEP flap harvest for breast reconstruction.
Keywords: robotic; microsurgery; DIEP